Greater male vulnerability to stunting? Evaluating sex differences in growth, pathways and biocultural mechanisms - Amanda L. Thompson (Taylor & Francis Group, 2021)
Context Child stunting has increasingly become the focus of large-scale global health efforts with the inclusion of stunting eradication as one of the Sustainable Development Goals of the United Nations. Child sex has been identified as a biological risk factor for stunting, and sex-specific approaches to stunting prevention have been proposed. Objective This paper examines four pathways, developmental sensitivity, energetics, caretaking and measurement, proposed to contribute to sex differences in linear growth faltering and stunting risk. Methods Anthropological, public health and clinical literature on sex differences in stunting and the mechanisms contributing to variability across contexts are reviewed. Results The direction of sex differences in stunting prevalence varies across countries and between households. Sex differences in growth trajectories and immune function beginning prenatally place boys at greater risk of infection and undernutrition, but these biological differences are interpreted by parents and within household contexts that are shaped by social and cultural norms which, in turn, influence care and feeding practices. Conclusion A perspective that incorporates an examination of the social and environmental factors shaping child growth in specific contexts is needed to understand sex-based vulnerability to stunting and to develop context-appropriate interventions.